Dinâmica territorial da comunidade ribeirinha de Santa Maria do Boiaçu – Rorainópolis/RR - Ramos, Sandra Elane de Souza Lauriano (2020)
The community of Santa Maria do Boiaçu, located in the Lower Rio Branco, city of Rorainópolis-RR, is a local that, throughout its social construction, was characterized by social occupations of varied domains and interests, responsible for its production and reproduction dynamics. Thus, this research aimed to analyze its territorial dynamics based on the systems of objects and local actions. The analysis of the geographical concepts "Space" and "Territory" and the understanding of the concept "Riverside Community" constituted the support and theoretical basis of this work. The adopted method was guided by the deductive strategy based on the qualitative and quantitative approach for carrying out explanatory, exploratory and descriptive research. Bibliographic and documentary surveys were carried out, appropriate to the theme addressed, and fieldwork using technical and instrumental procedures such as the application of questionnaires, oral surveys througt interviews and conversations, the use of the global positioning system (GPS), photographic and audiovisual records. Based on information collected and thematic maps elaboration, it was possible to understand the functioning of the community's territorial dynamics considering the space / time and the practice of spatial use and occupation from the analysis of the forms, functions, structures and processes found under existence control of political, social, economic and symbolic dimensions. The results of the research revealed the geo-historical panorama of the community, the location of the materialized intra-community elements and the analysis of the dynamics of the space promoting agents and their influence on the use and occupation of the territory. In addition, it also demonstrated that Santa Maria do Boiaçu has a polarizing synergy in relation to the other communities in its surroundings, considering the importance of its existing systems of objects and actions. Thus, it was concluded that the territorial dynamics of the Santa Maria do Boiaçu riverside community is due to the existence of relationships and domains of different social promoting agents that make use of natural resources, intra-community elements and public and private services.